2003
DOI: 10.1046/j.1432-1033.2003.03933.x
|View full text |Cite
|
Sign up to set email alerts
|

GTP cyclohydrolase I utilizes metal‐free GTP as its substrate

Abstract: GTP cyclohydrolase I (GCH) is the rate-limiting enzyme for the synthesis of tetrahydrobiopterin and its activity is important in the regulation of monoamine neurotransmitters such as dopamine, norepinephrine and serotonin. We have studied the action of divalent cations on the enzyme activity of purified recombinant human GCH expressed in Escherichia coli. First, we showed that the enzyme activity is dependent on the concentration of Mg-free GTP. Inhibition of the enzyme activity by Mg 2+ , as well as by Mn 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
1
9
1
1
Order By: Relevance
“…Furthermore, even when the apoenzyme is remetallated and then subjected to conditions designed to remove loosely bound metals (e.g., gel filtration), again only substoichiometric quantities of metal are detected (metal/protein mole ratios of 0.043 and 0.002 for Zn 2ϩ and Mn 2ϩ , respectively). These results are in marked contrast to those observed for GCYH-IA, in which Zn 2ϩ was observed to bind very tightly to the human enzyme (50) and incubation of the Zn 2ϩ -metallated enzyme with a variety of metal chelators failed to demetallate the enzyme and had no effect on catalytic activity. The results of those studies also showed that the enzyme was catalytically active with metal-free GTP, not metallated GTP.…”
Section: Resultscontrasting
confidence: 98%
“…Furthermore, even when the apoenzyme is remetallated and then subjected to conditions designed to remove loosely bound metals (e.g., gel filtration), again only substoichiometric quantities of metal are detected (metal/protein mole ratios of 0.043 and 0.002 for Zn 2ϩ and Mn 2ϩ , respectively). These results are in marked contrast to those observed for GCYH-IA, in which Zn 2ϩ was observed to bind very tightly to the human enzyme (50) and incubation of the Zn 2ϩ -metallated enzyme with a variety of metal chelators failed to demetallate the enzyme and had no effect on catalytic activity. The results of those studies also showed that the enzyme was catalytically active with metal-free GTP, not metallated GTP.…”
Section: Resultscontrasting
confidence: 98%
“…Studies suggested that divalent cations including magnesium, manganese, calcium and zinc have the capacity to modulate GTPCH1 activity (Hatakeyama et al, 1989) (Steinmetz et al, 1998) (Suzuki et al, 2004).…”
Section: (2) Cofactors: Divalent Cationsmentioning
confidence: 99%
“…To track phosphorylation of [8][9][10][11][12][13][14] C]AMP, the product [8-14 C]ADP was identified by chromatography on positively charged polyethylenimine (PEI)-cellulose under acidic conditions. A 20-l reaction mixture containing 110 mM potassium phosphate buffer, pH 6.0, 1.5 mM MgCl 2 , 60 mM KCl, 2 mM DTT, 0.25 M FeSO 4 , 2 mM cold AMP, 97 M [8-…”
Section: Shmt After the Transfer Of Methylene From L-[3-mentioning
confidence: 99%
“…Yet when similar systems were applied to the expression of P. falciparum proteins on a single gene or on a genome scale (6,7), the success rates, even loosely defined merely as the ability to make visible new protein, were less than 5%. In contrast, corresponding genes from human counterparts (8)(9)(10) or even from other parasitic sources are often readily overexpressed (11).…”
mentioning
confidence: 99%